2015
DOI: 10.14202/vetworld.2015.1078-1082
|View full text |Cite
|
Sign up to set email alerts
|

Detection and characterization of zoonotic dermatophytes from dogs and cats in and around Kolkata

Abstract: Aim:The ringworms of pet dogs, cats, and stray animals (dogs, cats, and other animals) could be a potential source of zoonotic infections causing a serious public health problem in the busy city Kolkata. The pet owners are more susceptible to get this infection from their pets, because of the close contact with them as dermatophytosis is very much prevalent in those pets. So, this study was aimed to check the prevalence of dermatophytosis in dogs, cats, and in pet owners.Materials and Methods:A total of 362 cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
0
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 16 publications
3
15
0
5
Order By: Relevance
“…The chronic infectious disease in the family members began with the hidden infections of their pets. There are more similar reports in the literature (Murmu et al 2015;Debnath et al 2016;Baumgardner 2017;Pasquetti et al 2017;Graser et al 2018;Neves et al 2018;Gnat et al 2018b). They demonstrate that the tendency towards keeping domestic animals and the possibility of asymptomatic infections in pets have an impact on the growing prevalence of dermatophytoses.…”
Section: Problems In Diagnosis and Treatment Of Dermatophytosesmentioning
confidence: 78%
“…The chronic infectious disease in the family members began with the hidden infections of their pets. There are more similar reports in the literature (Murmu et al 2015;Debnath et al 2016;Baumgardner 2017;Pasquetti et al 2017;Graser et al 2018;Neves et al 2018;Gnat et al 2018b). They demonstrate that the tendency towards keeping domestic animals and the possibility of asymptomatic infections in pets have an impact on the growing prevalence of dermatophytoses.…”
Section: Problems In Diagnosis and Treatment Of Dermatophytosesmentioning
confidence: 78%
“…The results of various studies concluded that the main species causing dermatophytosis in pets is Microsporum canis , in 81.8%-97% of the cases [ 1 , 2 , 6 ]. The incidence of zoonotic dermatophytes M. canis was the highest in dogs, cats, and human (60.0%) compared to other species [ 9 ]. High levels of cortisol over a long period of time modulate the immune response and induce immune suppression as the result of lymphatic tissue atrophy [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…This dermatophyte has been reported in rodents and less frequently in dogs and other mammals. Murmu et al in a previous study isolated in 16.7% from dogs' hair, skin and nails with suggestive lesions of dematophytoses [32]. In India Gangil et al, isolated T. mentagrophytes in 18.3% from dogs with skin lesions [33], while in Baghdad, Jasim isolated 30.95% in dogs, from samples taken from various body sites [34].These data contrast with our findings as we found a lower frequency that the previously cited authors, but this finding becomes relevant as it can be a source of infection or re-infection in human and animals, so better hygienic conditions are recommended to dogs´ owners as well as in places where animals are too close to each other (aesthetic canines and veterinary clinics).…”
Section: Discussionmentioning
confidence: 92%